Cu-In-Ga-S quantum dot composition-dependent device performance of electrically driven light-emitting diodes - Kim, Jong-Hoon; Lee, Ki-Heon; Jo, Dae-Yeon; Yangjin, Lee; Hwang, Jun Yeon; Yang, Heesun (AMER INST PHYSICS, 2014)
Colloidal synthesis of ternary and quaternary quantum dots (QDs) of In/Ga ratio-varied Cu-In1-x-Ga-x-S (CIGS) with nominal x = 0, 0.5, 0.7, and 1 and their application for the fabrication of quantum dot-light-emitting diodes (QLEDs) are reported. Four QLEDs having CIGS QDs with different compositions are all solution-processed in the framework of multilayered structure, where QD emitting layer is sandwiched by hybrid charge transport layers of poly(9-vinlycarbazole) and ZnO nanoparticles. The device performance such as luminance and efficiency is found to be strongly dependent on the composition of CIGS QDs, and well interpreted by the device energy level diagram proposed through the determination of QD valence band minima by photoelectron emission spectroscopic measurement. (C) 2014 AIP Publishing LLC.